Need for vape warning label - Ser, Hooi Leng *; Amar, Daud Iskandar Abdullah *; Long, Chiau Ming *; Look, Keyun (New Straits Times Press (M) Bhd., 2023)
LETTERS: The lack of adequate labelling on vape liquids, also known as e-liquid or e-juice, has contributed to an increase of acute nicotine poisoning among children.